Biology of Trypanosoma cruzi - De Souza, Wanderley (IntechOpen, 2019)
Trypanosoma cruzi, an important zoonotic protozoan that causes Chagas disease, affects at least 8 million people in Latin America. Chagas disease is an important life-long infection in humans that can be divided into distinct clinical stages: the acute phase, where patient symptoms can vary from asymptomatic to severe; the indeterminate form, which is usually asymptomatic; and the chronic phase, where cardiomyopathy and/or digestive megasyndromes appear. In addition to its medical importance, T. cruzi is an interesting biological model for studying processes such as: (1) cell differentiation, where a non-infective stage transforms into an infective one; (2) cell invasion, where the infective stages are able to penetrate into a mammalian host cell, where they multiply several times and thus amplify the infection; and (3) evasion from the immune system, using several mechanisms. This book, with 13 chapters, has been organized in four major sections: 1. "Basic Biology," 2. "Biochemistry and Molecular Biology," 3. "Parasite"Host Cell Interaction," and 4 "Chemotherapy." The chapters include basic biological information on the protozoan lifecycle, including new information on parasite genomics and proteomics. In addition, they analyze the interaction with host cells as well the immune response and evasion, ending with information on experimental chemotherapy against Chagas disease.